2020
DOI: 10.1016/j.msea.2020.139452
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent strengthening contributions in austenitic and ferritic ODS steels

Abstract: We aim on the model-based description of the strength of ferritic and austenitic oxide dispersion strengthened (ODS) steels in the temperature range from room temperature (RT) up to 800 °C. Therefore, we present two approaches for the synthesis of austenitic alloys by mechanical alloying Y2O3, namely with (i) elemental powders at RT and (ii) with a gas-atomized master-alloy. Consolidation of both powders by field assisted sintering technique leads to a more homogenous distribution of grain size and particles i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 94 publications
2
23
1
Order By: Relevance
“…The Cr contents of 12 wt pct or higher promote resistance to corrosion, while the ODS nanoparticles are responsible for the good mechanical performance of the steels at high temperatures and for their resistance to radiation damage. [1][2][3][4][5][6][7][8][9][10] Conventional fabrication routes of ODS ferritic steels involve mechanical alloying, consolidation by extrusion or hot isostatic pressing and further thermo-mechanical processing (cycles of cold rolling and annealing, hot rolling, hot forging). [1][2][3]6] The microstructure of ODS ferritic steels consolidated via extrusion is composed of large, elongated grains and nanosized grains.…”
Section: Introductionmentioning
confidence: 99%
“…The Cr contents of 12 wt pct or higher promote resistance to corrosion, while the ODS nanoparticles are responsible for the good mechanical performance of the steels at high temperatures and for their resistance to radiation damage. [1][2][3][4][5][6][7][8][9][10] Conventional fabrication routes of ODS ferritic steels involve mechanical alloying, consolidation by extrusion or hot isostatic pressing and further thermo-mechanical processing (cycles of cold rolling and annealing, hot rolling, hot forging). [1][2][3]6] The microstructure of ODS ferritic steels consolidated via extrusion is composed of large, elongated grains and nanosized grains.…”
Section: Introductionmentioning
confidence: 99%
“…Originally, ferritic ODS steels were introduced as possible candidates for cladding materials in future nuclear fission and fusion power plants [1][2][3] for which among others the high corrosion resistance [4][5][6], the high resistance against irradiation caused swelling [7-10] and superior creep resistance compared to common high temperature steels [1,2,11] were decisive. In recent years, the interest in austenitic ODS steels increased [12][13][14][15][16]. Due to their close-packed, face-centered cubic (FCC) crystal structure, they are expected to provide even higher creep strength in comparison to their ferritic counterparts in the high temperature range above 600 °C [14,17].…”
Section: Introductionmentioning
confidence: 99%
“…The extraordinary properties of ODS steels are mainly related to nano-scaled oxides, so-called nanoclusters, usually less than 4 nm in size [18][19][20][21][22]. To obtain a homogenous distribution of these nanoclusters in the material, mechanical alloying (MA) of yttria powder with elemental or pre-alloyed metallic powders and subsequent consolidation by hot extrusion [1,2,23], hot isostatic pressing (HIP) [20,21], or field assisted sintering technique (FAST) [16,24,25] are typically applied. In contrast to hot extrusion or HIP, FAST allows for short consolidation times, which prevent coarsening of grains and/or ripening of nano-scaled oxides during consolidation and leads to equiaxed, ultra-fine grains without preferential orientation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Schneibel et al [10] reported that the materials having a stable fine grain structure exhibited high grain boundary strengthening (i.e., indirect strengthening) even at above homologous temperature of 0.5. Recently, Seils et al [42] investigated the temperature-dependent strengthening contributions in austenitic and ferritic ODS steels from RT to 1073 K. These authors reported that above the transition temperature, deformation was possibly dominated by generation and annihilation of dislocations at grain boundaries. Based on these inferences, in the present work, the models which have taken the thermal activation into account are considered (discussed in detail in Section III-E-B).…”
Section: Introductionmentioning
confidence: 99%